Enhancing surface properties of circular carbon biochar derived from spent coffee beans through ZnCl2/KOH activation - D., Gowthami; Sharma, R.K; Mohammad, Khalid; Muhammad Yusri, Ismail (Springer, 2025)
In this work, biochar was synthesized by carbonizing spent coffee grounds by conducting oxygen-limited pyrolysis in a muffle furnace. Six varieties of biochar have been synthesized at 550 ℃ and 750 ℃ with a ramp rate of 10 ℃/min and carbonization time of 120 min. Acid- and alkali-activated biochars were produced by carbonizing the activated biomass at 550 ℃ and 750 ℃. ZnCl2 and KOH were used as activating agents for acid and alkali activation, respectively. All the synthesized biochar yield was recorded as 40–60 wt% of the biomass weight. BET surface area increased significantly after activation and the values varied between 1.01 and 720.52 m2/g. The process of chemical activation has resulted in increased BET surface area in comparison with the pristine biochar. Other characterizations include FESEM analysis, elemental analysis through EDX, FTIR, UV–visible spectroscopy, XRD analysis, TGA, and Raman spectroscopy. Raman spectra and UV–visible spectra of activated samples revealed a higher graphitic quality and absorbance, respectively, whereas XRD analysis demonstrated the changes in structural phases. Activated carbon based on spent coffee grounds has displayed higher thermal stability and better surface chemistry than pristine biochar, enabling its application in various domains that foster circular economy.